2012
DOI: 10.1186/1476-0711-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity pattern among bacterial isolates in neonatal septicaemia in port Harcourt

Abstract: BackgroundThe organisms responsible for neonatal sepsis vary across geographical boundaries and with the time of illness thus periodic bacteriologic surveillance is a neccessity. The present study was therefore carried out to determine the common bacterial pathogens in Port Harcourt and their sensitivity pattern.MethodsFour hundred and six neonates were prospectively screened for sepsis over a 6 month period. Sensitivity of the bacterial isolates to different antibiotics was determined using Kirby-Bauer diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
26
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 9 publications
11
26
5
Order By: Relevance
“…Lancefield grouping is not done in our institution. Similar to our study Klebseilla is found most common organism in study done by Desai et al 9 (47.14%), Rathore et al 10 (55.14%), West Peterside et al 11 (58.2%). In study in third generation cephalosporins only one organism (Strept.…”
Section: Discussionsupporting
confidence: 91%
“…Lancefield grouping is not done in our institution. Similar to our study Klebseilla is found most common organism in study done by Desai et al 9 (47.14%), Rathore et al 10 (55.14%), West Peterside et al 11 (58.2%). In study in third generation cephalosporins only one organism (Strept.…”
Section: Discussionsupporting
confidence: 91%
“…16 Much higher rates of neonatal LCBI (33.1%) were reported from a Nigerian special care infant unit. 17 Many studies report on blood culture yield, rather than result of the predominance of late-onset neonatal sepsis. Most neonates were given empirical antibiotics at birth for prematurity, or had experienced an earlier episode of suspected sepsis.…”
Section: Prevalence Of Neonatal Septicaemiamentioning
confidence: 99%
“…Our study and others from Africa report a higher prevalence of late-onset neonatal sepsis. 12,17,23,24 This pattern represents horizontal infection transmission, i.e. hospitalacquired infections, which are largely preventable by good infection control practices.…”
Section: Timing Of Neonatal Septicaemiamentioning
confidence: 99%
“…Neonatal nurseries in some LMICs report meticillin resistance rates of 17-28% in S aureus isolates. 40,216,237 Similarly, Lubell and colleagues 238 recorded poor susceptibility to almost all commonly used antibiotics in pathogens such as S aureus and Klebsiella spp. Without rigorous evidence, most clinicians agree that 90% susceptibility or higher of potential pathogens to antibiotics in critical care settings like neonatal intensive care units, and 80% or higher in non-critical health-care settings, is acceptable.…”
Section: Neonatal Sepsismentioning
confidence: 99%